Respuesta :

Answer:

=z ^(-11) + ^(-15)

= z ^ -26

Answer:

z^-11 times z^-15 = z^-26

Step-by-step explanation:

According to exponential properties, multiplying two numbers that have exponents with the same bases should be added.

Negative exponents mean to go from a^-x to 1/a^x.

Using these properties, we evaluate the expression.

Both terms have the same base, z, so we can go ahead and add the exponents.

-11 + -15 = -26

z^-11 * z^-15 = z^-26

Because the instructions specifically say to leave it in z^n form, our answer is z^-26.

Hope this helped!!